Application of the C4.5 Algorithm in Teaching Teachers' Skills on Learning Effectiveness - Sari, Feby Widya; Safii, M. (Yayasan Kita Menulis, 2021)
Teachers as educators and education personnel have a very important role in improving the quality of education in schools. In an effective teaching and learning process, teacher skills in teaching are very important. This study aims to classify the skills of teachers in SMA Yayasan Pendidikan Keluarga using the Decision Tree method with the application of the C4.5 Algorithm in order to improve the teaching system in an effort to increase students' understanding of the learning process. In determining the teaching skills of teachers, classification is carried out into the labels